3w⋅w=48

Raise w to the power of 1.

3(w1w)=48

Raise w to the power of 1.

3(w1w1)=48

Use the power rule aman=am+n to combine exponents.

3w1+1=48

Add 1 and 1.

3w2=48

3w2=48

Divide each term in 3w2=48 by 3.

3w23=483

Cancel the common factor of 3.

Cancel the common factor.

3w23=483

Divide w2 by 1.

w2=483

w2=483

Divide 48 by 3.

w2=16

w2=16

Take the square root of both sides of the equation to eliminate the exponent on the left side.

w=±16

Simplify the right side of the equation.

Rewrite 16 as 42.

w=±42

Pull terms out from under the radical, assuming positive real numbers.

w=±4

w=±4

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

w=4

Next, use the negative value of the ± to find the second solution.

w=-4

The complete solution is the result of both the positive and negative portions of the solution.

w=4,-4

w=4,-4

w=4,-4

Solve for w 3w*w=48